DAMPAK FAKTOR INTERNAL DAN EKSTERNAL TERHADAP HARGA SAHAM SEKTOR INFRASTRUKTUR - Dwijayati, Bonita Restu; Robiyanto, Robiyanto (International Journal of Social Science and Business, 2020)
This research aims to test the impact of internal and external factors both simultaneously and partially against the stock price of infrastructure sectors. Research using quantitative methods. The population in this study is the entire infrastructure, utilities and transportation company listed on the Indonesia Stock Exchange in the period 2014-2018. The sample selection technique is using the purposive sampling method. Based on predefined criteria, acquired 30 companies are being sampled. Data analysis techniques use a regression analysis of data panels. The results showed that the simultaneous variables of the DPR, NPM, CCC and interest rates had significant effect on the stock price of infrastructure sectors. As for the partial, the variables of the DPR and NPM positively influence insignificant against the stock price. On the other hand the CCC variables have significant negative effect on the stock price and the interest rate is significantly positive against the stock price.